Labour market research for an ageing workforce in times of digitalisation - Scoppetta, Anette [Verfasser]; Naegele, Laura [Verfasser]; Varlamova, Maria [Verfasser] (My University, 2024)
„This chapter explores the transformation of labour markets due to digitalisation and its impact on the ageing workforce. The ongoing integration of digital technologies and data across the economy and society affects the content, organisation, design, regulation and protection of work, but also how we learn and develop competencies. Therefore, the company level is significant as it provides ‘the places of work’ and shapes the creation of age-inclusive work and learning environments enabling lifelong learning and extended working lives. Fields of tension in digital labour markets are scrutinised at the macro-, the meso- and micro-level. Necessary changes are discussed to enable a human-centric, age-friendly transformation where no one is left behind. Options comprise adaptations of the work environment, including combating ageism and changes in management approaches and practices, targeted investments in education, training and capacity building for upskilling and reskilling workers, and profound reforms of (social) policy systems.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 2.2.1 Technologisierung; G 2.3.1 Arbeitsteilung & -organisation; 370; Arbeitsmarkt; Digitalisierung; Auswirkung; Erwerbstätiger; Älterer Arbeitnehmer; Arbeitsgestaltung